Epidemiology of injuries in female and male senior Slovenian handball leagues - Baric, A.; Hlebs, S.; Novak, S.; Brumat, P. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Handball is associated with a high frequency of injuries due to unexpected situations, external disturbances of movement and extreme positions of body segments. The purpose of this study was to identify and analyze injuries among female and male players from all five senior Slovenian handball leagues in the season 2010/2011. METHODS: We conducted a retrospective epidemiological study using a questionnaire. Data were collected between February and May 2012. Descriptive analysis is provided. RESULTS: Forty-five percent of all the players were injured, reporting 92 injuries. 0.58 injuries/player occurred, 57 (62%) in females and 35 (38%) in males. Injury incidence in females (27.7 injuries/1000 hours match, 0.97 injuries/1000 hours training) was higher than in men (10.6 injuries/1000 hours match, 0.5 injuries/1000 hours training), respectively. The left- and right-back players were injured most often (41%). Sprain was the most common injury type (55%). Most injuries were severe (29%). The lower limb was injured most frequently (62%). Ankle was injured the most commonly (35%), but ankle injuries were in most cases moderate (38%). More than 70% of knee injuries and 50% of shoulder injuries were severe. In 33%, cause of injury was contact with an opponent/teammate. Thirty-six percent of players reported shoulder and 36% ankle overuse syndromes. CONCLUSIONS: Present findings showed a higher incidence of injuries in female than in male senior Slovenian handball players in the 2010/2011 season. Preventive programs should focus not only on the acute ankle and knee injuries, but also on overuse syndromes of the shoulder and ankle.